Implementasi Pembelajaran Dengan Strategi Konflik Kognitif Berbantuan Aplikasi Augmented Reality Dalam Meningkatkan Kemampuan Pemecahan Masalah Matematis Pada Siswa SMP Negeri 4 Percut Sei Tuan - Rusmini, Rusmini; Fitrah Sari Wahyuni Harahap; Doni Irawan Daragih; Adinda Dwi Arwilla; Fauziah Zahra Pane (Sekolah Tinggi Teknologi Industri (STTI) Bontang, 2024)
Mathematical problem solving is the process of solving problems or problems using concepts, principles and methods related to mathematics. Mathematical problem-solving ability is the skill to use mathematical concepts and strategies in solving real problems. Students' mathematical problem-solving abilities can increase with the implementation of learning assisted by Augmented Reality (AR). The aim of this community service is to implement learning media with AR-assisted cognitive conflict strategies. Does the implementation of this media affect students' mathematical problem-solving abilities regarding cubes and blocks. This community service was carried out at SMP Negeri 4 Percut Tuan for class VIII students, where each class took 5 people as representatives and the number of students who took part in the socialization process was 25 people. Activities are carried out in stages 1) socialization of AR-assisted learning media, 2) Implementation of AR-assisted learning media, 3) evaluation by providing a pre-test before implementation and providing a questionnaire, post-test after implementation. Based on the results of the questionnaire, the implementation of learning media with AR-assisted cognitive conflict strategies motivates students and strengthens understanding of concepts so that it has an impact on students' mathematical problem-solving abilities. The pre-test and post-test data were carried out by the N-Gain test, there was an increase and the t test showed differences between before and after implementation. This means that there is a significant influence from the implementation of learning media with AR-assisted cognitive conflict strategies on students' mathematical problem-solving abilities. Keywords: Implementation, Learning Media, Augmented Reality, Mathematical Problem Solving Ability.